2002
DOI: 10.1002/art.10566
|View full text |Cite
|
Sign up to set email alerts
|

Self epitopes shared between human skeletal myosin and Streptococcus pyogenes M5 protein are targets of immune responses in active juvenile dermatomyositis

Abstract: Objective. To identify self T cell epitopes associated with proinflammatory immune responses and clinically active juvenile dermatomyositis (juvenile DM). The target of our search for relevant epitopes was represented by amino acid sequences shared between human skeletal myosin and Streptococcus pyogenes M5 protein. The long-term objective of the project is to identify suitable targets for immunotherapy of the disease.Methods. We used computerized algorithms to identify putative agretopes on both the human myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 43 publications
2
27
0
3
Order By: Relevance
“…2). Thus, as in the other models tested before, TCC provided a very effective tool to enumerate and characterize dnaJP-specific T cells in PBMCs from patients with RA (22,25,27).…”
Section: Mucosal Tolerization To Dnajp1 Leads To a Peptide-specific Imentioning
confidence: 76%
See 1 more Smart Citation
“…2). Thus, as in the other models tested before, TCC provided a very effective tool to enumerate and characterize dnaJP-specific T cells in PBMCs from patients with RA (22,25,27).…”
Section: Mucosal Tolerization To Dnajp1 Leads To a Peptide-specific Imentioning
confidence: 76%
“…To address this question directly, we enumerated dnaJP1-specific T cells by TCC, a recently described method, based on aAPCs. We and others (22,(25)(26)(27) showed that these aAPCs can effectively bind low-affinity polyclonal MHC class II-restricted CD3ϩ T cells, thus providing an excellent tool to characterize antigen-specific CD4 ϩ T cells. This task is very difficult to achieve by using state-of-the-art MHC tetramer technology.…”
Section: Mucosal Tolerization To Dnajp1 Leads To a Peptide-specific Imentioning
confidence: 98%
“…A streptococcal M protein peptide (aa 367-375) and its myosin homolog (aa 114-122) selectively stimulated JDM lymphocytes (cytotoxic response, increased lymphocyte proliferation, and tumor necrosis factor ␣ production) when JDM peripheral blood mononuclear cells were compared with controls (6); stimulation that is compatible with immune activation (37). In addition, these streptococcal peptides also elicited limited T cell receptor V␤ usage (12,15,18) using a T cell capture analysis (6). Further evidence for an activated immune response compatible with a preceding infection in JDM is obtained from gene expression profiles of muscle of untreated children with JDM, which show an increase in IFN-␣/␤ inducible immune genes (9).…”
Section: Pachman Et Almentioning
confidence: 99%
“…Previously, we described artificial APC (aAPC) in which MHCpeptide complexes were randomly distributed within the aAPC membrane (16,17). These aAPC were prepared by inserting affinity-purified MHC molecules containing their transmembrane domain in highly fluid lipid bilayers.…”
mentioning
confidence: 99%